Synthesis, characterization and sorption properties of microporous titanosilicate ETS-10 from rice husk ash - Jei, Ching Yih (2008)
A new class of nano-sized microporous titanosilicate ETS-10 has been prepared through hydrothermal synthesis route in the absence of ETS-4 and organic template agent. Local agriculture waste â€“ rice husk ash (RHA) has been used as the silica source and commercial titanium oxide namely P25 as titanium source. For comparison, the colloidal silica source, LUDOX-30 was also used as a silica source to synthesize the ETS-10. The influence of some synthesis parameters such as synthesis time and heating temperature on the crystallization of ETS-10 and the gel oxides composition have also been investigated. The physico-chemical characterization of these synthesized materials have been carried out by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), UV-Vis spectroscopy (UV-VIS), Field Emission Scanning Electron Microscopy (FESEM), Solid State Nuclear Magnetic Resonance (NMR), nitrogen adsorption-desorption analysis and Raman spectroscopy. The best ETS-10 sample was successfully obtained under heating at 220Â°C for 52 hours using the following molar ratio TiO2 : 3.75SiO2 : 1.5NaOH : 0.54KF : 21.25H2O. The ability of the synthesized ETS-10 as adsorbents for heavy metal ion such as Pb2+, Cd2+ and Cu2+ was investigated. The study of equilibrium and adsorption isotherm at 298 K was conducted using batch mode. The uptake rates for these heavy metal ions were extremely fast and fitted well with the pseudo-second order model and Langmuir equation with an affinity order of Pb2+ > Cd2+ > Cu2+, with values of 1.86, 1.51 and 1.45 mmol/g respectively, which are the highest adsorptive capacities of the heavy metal ions on zeolite materials reported so far. This indicates that ETS-10 is a very promising adsorbent for divalent heavy metals.